Effect of short carbon fiber surface treatment on composite properties - Vishkaei, Mahta Sadegh; Mohd Salleh, Mohamad Amran; Yunus, Robiah; Awang Biak, Dayang Radiah; Danafar, Firoozeh; Mirjalili, Fatemeh (SAGE Publications, 2010)
The effects of whiskerized carbon fibers (WCF) embedded as filler into polymer matrix were investigated. In this respect, composites consisting of pure polypropylene and also carbon fiber (CF)/polypropylene (PP) was fabricated and compared. Polypropylene matrix was reinforced with 2% concentration of WCF and prepared by a melt-mixing method. The tensile test indicated that the addition of 2% WCF enhanced the tensile strength and Young’s modulus by 38.1% and 28.2%, respectively. Besides that, the elongation was decreased for that sample. Dynamic mechanical analysis showed an increase of 39.2% in the stiffness of the WCF/PP composite and an improvement in the storage modulus. The tan δ for the sample was also smaller than unfilled PP and CF/PP composites. Furthermore, thermogravimetric analyses in an inert atmosphere showed a shift of temperature to the higher temperature with the addition of fillers.